2021
DOI: 10.1002/nme.6749
|View full text |Cite
|
Sign up to set email alerts
|

Fourier transform approach to nonperiodic boundary value problems in porous conductive media

Abstract: In this article, we develop an extension of the Fourier transform solution method in order to solve conduction equation with nonperiodic boundary conditions (BC). The periodic Lippmann-Schwinger equation for porous materials is extended to the case of non-periodicity with relevant source terms on the boundary. The method is formulated in Fourier space based on the temperature as unknown, using the exact periodic Green function and form factors to describe the boundaries. Different types of BC: flux, temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Based on previous works for porous material (To and Bonnet, 2020;To et al, 2021), the new LS governing equations can be derived when the pore tends to the crack limit. In this case, the temperature jump and the heat flux jump are unknown and can be solved in the new formulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous works for porous material (To and Bonnet, 2020;To et al, 2021), the new LS governing equations can be derived when the pore tends to the crack limit. In this case, the temperature jump and the heat flux jump are unknown and can be solved in the new formulation.…”
Section: Discussionmentioning
confidence: 99%
“…In the present paper, a FFT method dealing with cracks of zero thickness is presented. We note that the case of finite insulating pore can be treated by LS equations derived for skeleton temperature (To and Bonnet, 2020;To et al, 2021). It suggested that the method could be extended to insulating and superconductive cracks.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the integral equations to solve the heat transfer problem with source term can be obtained (To et al , 2021). Depending on the choice of unknowns, we have, say, for gradient e : for the flux j : and for the polarization τ : …”
Section: Fourier Transform Resolution Methods Using Static Green Tensormentioning
confidence: 99%
“…The method can be extended to nonperiodic problems where the source term can be used to impose heat flux and temperature, for example the immersed interface technique (Peskin, 1972;LeVeque and Li, 1994;Wiegmann, 1990). The details of FT implementation using form HFF 33,6 factor and continuous Green tensors can be found in a recent work (To et al, 2021). Another possibility is to use polarization (or eigenstress/strain for elasticity) as done by Gelebart (2020) or Chen et al (2019).…”
Section: Iteration Schemesmentioning
confidence: 99%
See 1 more Smart Citation